Catalytic Conversion of Ethanol into an Advanced Biofuel: Unprecedented Selectivity for n‐Butanol1. Issue 34 (10th July 2013) - Dowson, George R. M.; Haddow, Mairi F.; Lee, Jason; Wingad, Richard L.; Wass, Duncan F.
<x xml:space="preserve">Abstract</x> Taming the beast: Unprecedented selectivity of over 94 % at good (20 %+) conversion was observed for the upgrade of ethanol to the advanced biofuel 1‐butanol with a ruthenium diphosphine catalyst (see picture; P orange, Ru blue). Preliminary mechanistic studies indicate that control over the notoriously uncontrolled acetaldehyde aldol condensation is critical for the high selectivity, and evidence was found for an on‐metal condensation step.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>